Strategy 2020: New Outlines of Russian Innovation Policy - Leonid Gokhberg; Tatiana Kuznetsova (Foresight and STI Governance, 2011)
The paper reviews the work of the expert group “The transition from fostering innovation to innovation-based growth” on adjusting the Strategy for socio-economic development of Russia up to 2020. Panel experts have undertaken a detailed analysis of the state of the art of the Russian innovation sphere and proposed recommendations on the strategic priorities for state policy, as well as on specific regulatory tools that can be implemented in the near future.